BOTTOMWATER FORMATION DUE TO HYDROTHERMAL ACTIVITY IN FROLIKHA BAY, LAKE BAIKAL, EASTERN SIBERIA - Kipfer R.; Aeschbach-Hertig W.; Hofer M.; Hohmann R.; Imboden D.M.; Baur H.; Golubev V.; Klerkx J. (My University, 1996)
Hydrothermal water enters Frolikha Bay, a well-known site of high geothermal heat flux in the northern part of Lake Baikal, at 400 m depth. On the basis of CTD profiles, the hydrothermal water is identified as forming an anomalous bottom layer with a higher temperature (>0.15 °C) and salinity (>2.5 mg · kg−1) than the overlying water. Due to the entrainment of lake water, a distinct dense water layer up to 40 m thick, stabilised by its slightly higher salinity, becomes established close to the bottom of the bay. The density current thus generated flows out of the bay towards the deeper parts of the basin. Since helium isotope analysis shows that the geochemical characteristics of the hydrothermal water are similar to those of water from nearby hot springs on land, the bottomwater of Frolikha Bay is easily interpreted in terms of the mixing of ordinary fresh water from the lake and hydrothermal water carrying isotopically heavy He from the continental crust. Because of its high crustal He content, a similar hydrothermal component may even be identified in the open water of the northern basin.